ENHANCEMENT OF SOLUBILITY AND OPTIMIZATION OF ORALLY DISINTEGRATING FILMS OF ACYCLOVIR - Pandey, Bikash; Khan, Arshad Bashir (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this work was to prepare and optimize orally disintegrating films of acyclovir (ACV), which is a known antiviral agent. To enhance the solubility of ACV, solid dispersions of ACV were made. Methods: The films were prepared using a solvent casting technique. Full factorial design was utilized for the optimization of the effect of independent variables such as the amount of hydroxypropyl methylcellulose 5 cps, sodium starch glycolate, and propylene glycol on the disintegration time. Other evaluation tests such as drug release, drug content, thickness, and folding endurance of film were also conducted. Results: Compatibility studies by Fourier transform infrared showed that there was no significant interaction between the drug and excipients used. Disintegration time was found to be 43 s for the optimized batch. The in vitro release profile of formulation response disintegrating time in phosphate buffer pH 6.8 revealed that there was a significant increment in drug release of the optimized batch in comparison to the screening batches. Further, short-term accelerated stability studies carried out for 4 weeks for the optimized formulation which proved that the formulated films were stable at the accelerated conditions of temperature and humidity (40±2°C/75±5% RH). Conclusions: It was concluded that such ACV solid dispersion films could be beneficial in enhancement of dissolution and consequently the oral bioavailability of ACV.